The appearance of old age in the documents regulating artificial intelligence of the European Union and Hungary - Imre; Balázs (Magyar Gerontológia, 2025)
In our paper, we review the most important domestic (Government Resolution 1573/2020. (IX. 9.) on the Artificial Intelligence Strategy of Hungary and certain measures necessary for its implementation; Artificial Intelligence Strategy of Hungary) and European Union (e.g. White Paper on Artificial Intelligence: a European approach to excellence and trust; Regulation (EU) 2024/1689 of the European Parliament and of the Council on the establishment of harmonised rules on artificial intelligence…) legal and strategic documents from a gerontological perspective.